We were invited to friendships: Lived hospitality - Rønsdal, Kaia S. (Approaching religion, 2020)
This article explores hospitality in relation to migration within the framework of spatial theory and calling. The material of the article is based on fieldwork carried out in the Nordic borderlands and conducted in relation to a research project exploring Nordic hospitality. The concept and context of the borderland, as well as the methodological development of this project, are based on spatial theory, phenomen-ology and theology. The material discussed are excerpts from a small fieldwork narrative about borderland experiences, and interviews regarding events that took place on the Russian-Norwegian border during the so-called refugee crisis in 2015-16. The article aims at, by means of these narrative excerpts, exploring how conceptualisations of hospitality, by discussing them in relation to the concept of calling from Scandinavian creation theology, may contribute to extensions of both concepts.